THE LINGUISTIC FEATURES OF PHRASEOLOGICAL UNITS IN DEVELOPING WORD FORMATION IN ENGLISH - Muxiddinova Saboxat Axmadjanovna (PEDAGOGS, 2025)
Phraseological units (PUs) are combinations of words that function as single lexical items, often with meanings that cannot be deduced from the individual words they contain. Commonly referred to as idiomatic expressions or fixed phrases, these units are a crucial aspect of language, especially in English, where they contribute significantly to the richness and versatility of communication. Examples of phraseological units include expressions like "a piece of cake" (meaning something easy) and "break the ice" (to initiate a conversation in a social setting).In the context of word formation, phraseological units offer insight into how language evolves and how new words and expressions emerge. This article examines the linguistic features of phraseological units, focusing on their role in the development of word formation in English. We will explore how these units contribute to morphological processes, enrich lexical semantics, and influence the dynamics of word creation.